The Impact of the Long-Term Care Insurance on the Medical Expenses and Health Status in China - Tang, Yao; Chen, Tianran; Zhao, Yuan; Taghizadeh-Hesary, Farhad (Frontiers in Public Health, 2022)
Based on the panel data of China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2015, and 2018, this paper used the difference-in-difference (DID) method to evaluate the implementation effect how the Long-Term Care Insurance (LTCI) policy impacted on the medical expenses and the health status of the middle-aged and elder population. The empirical results show that LTCI has reduced the outpatient and inpatient quantity by 0.1689 and 0.1093 per year, and cut the outpatient and inpatient expenses by 23.9% and 19.8% per year. Moreover, the implementation of LTCI has improved the self-rated health, the activity of daily living (ADL), as well as the mental health. These conclusions verify the implementation value of LTCI system and provide policy implications for the medical reform and the further LTCI implementation in a larger scale.